Movements in Yields, Not the Equity Premium: Bernanke-Kuttner Redux - Stefan Nagel; Zhengyang Xu (CESifo GmbH, 2024)
We show that the stock market price reaction to monetary policy surprises upon announcements of the Federal Open Market Committee (FOMC) is explained mostly by changes in the default-free term structure of yields, not by changes in the equity premium. We reach this conclusion based on a new model-free method that uses dividend futures prices to obtain the counterfactual stock market index price change that results purely from the change in the default-free yield curve induced by the monetary policy surprise. The yield curve change in turn partly reflects a change in expected future short-term interest rates, as measured by changes in professional forecasts, and partly a change in the term premium. We further find that the even/odd week FOMC cycle in stock index returns is also largely due to an FOMC cycle in the yield curve rather than the equity premium.
Keywords: G12; E52; 330; monetary policy; equity premium; yield curve; dividend futures; term premium